Measurement of Ethics among Engineering Students - Palaninatha Raja, M.; Abirami, A. M. (Journal of Engineering Education Transformations, 2017)
Ethics is an important attribute for any professions like engineering, medicine, legal and so on. Despite its importance, ethics has come down among the engineers in the recent past and the day to day events in the nation witnesses the engineering as collapsible or substandard bridges, development of illegal arms, unworthy clothing for uniformed people, etc,. Engineering Ethics is introduced into curriculum and the students are assessed and evaluated theoretically as per the legal directions. This loses the focus and the purpose of ethics. Engineering ethics is an important outcome specified in the Graduate Attributes of Accreditation at national and international level. Specifically, the code of conduct or the behavior of student could be measured based on the identified and well proven ethical principles. Questionnaire has been prepared against eleven basic principles of ethics. Students' thinking on each of these principles is measured through 1-5 likert scale. Face validity is adopted in this survey. It is an indirect assessment method which enables to achieve the objective of assessing the ethical behavior of engineering students. The results show that the actual thinking on ethical practices and their emotions have been captured and reported among engineering students.